A (re) look at the (post) Apartheid experience of Black people in South Africa: from the perspective of the Township people of Soweto - Letlonkane, Katlego (My University, 2021)
The present study is an examination of the (post)-apartheid experience of the people of South Africa understood from the specific case of a sample of the township people of Soweto. The study is, theoretically speaking, acritical diversity research project, which suggests, or at least opens the door to the creation and production of knowledge of a different kind. This work is rooted in the social, in the nuanced elements of life as is experienced by some selected people, selected primarily on the basis of their race, historically classified as Black people under institutionalized apartheid structure. By looking through a sample of individuals sharing some of their personal experiences growing up through some of the legacies of apartheid. The (post) apartheid reality in South Africa has been troubled widely for the intensified and prolonged maltreatment and segregation of marginalized communities in South Africa, particularly, Black South Africans. Critical social study allows useful exploration into some of the human complexities inherited from apartheid. This research paints a picture and guides a more contextual reading of the lives, I gather, a large number of Black South Africans are living in some or other location in Soweto, lead in (post) apartheid South Africa (today). Soweto itself as a colonial legacy presents a useful opportunity as a site for research in a project of this nature. I bracket post to trouble the notion of an ended apartheid. A central aim of this research is to study apartheid and its remaining legacy, examining how the lives of people are still pre and over determined by apartheid structure. It is the intention of this work, to trace the extents of inequality (as a central instrument of apartheid), as it played and seemingly, (given the alarming reality that over half of South Africa's population lives in poverty) continues to play itself out on the lives of those, who were subjected to racism and racist oppression in South Africa. I center this research in the location and on the disempowered. This work is undertaken with the intention for it to contribute to the post-apartheid jurisprudence produced with the vision to critically engage with and bring critical thinking to the level of the social to evaluate how much of present-day life in South Africa continues to be pre and over determined by the machinery of apartheid
A research report submitted in completion of an Interdisciplinary MA in Critical Diversity Studies, for the Faculty of Humanities, University of the Witwatersrand: Centre for Diversity Studies, 2021